Model Reduction of the Flexible Rotating Crankshaft of a Motorcycle Engine Cranktrain - Stefano Ricci; Marco Troncossi; Alessandro Rivola (International Journal of Rotating Machinery)
This paper addresses the development of an elastodynamic model of a motorcycle engine cranktrain aimed at accurately evaluating the interactions between the crankshaft and the engine block, thus allowing an improved structural design. A rigid multibody model is first implemented and simulated; only kinematic joints are involved at this stage, leading to a statically determinate assembly of the mechanism. Such a modelling approach prevents the loads at certain interface locations to be evaluated; furthermore, high-frequency dynamic effects cannot be predicted. These drawbacks can be removed by introducing bushing-like elements and/or modelling component flexibility. In this paper, this latter aspect is the objective of the investigation; in particular, a finite element model of the crankshaft is implemented as a replacement for the corresponding rigid member. The well-established Craig-Bampton model reduction technique is used to represent the elastodynamic behaviour of the component with a limited number of coordinates. The mode selection procedure is emphasized here: a measure of modal dynamic importance, namely the effective interface mass fraction, is used to rank fixed-interface normal modes based upon their contribution to loads at the substructure interface; choosing the modal base according to such ranking leads to a minimal yet accurate representation.